Depositional Environment and Diagenesis processes impact on the carbonate rock quality: a case study, southeastern of Iraq - Saleh, Afrah Hassan (Iraqi Journal of Science, 2019)
Deposition environment and diagenesis processes are very important factors which affect and control the reservoir properties. The carbonate Mishrif Formation has been selected as a carbonate reservoir in selected wells from southeastern Iraq to understand the influence of the Deposition environment and diagenesis processes on the carbonate reservoir. A core examination of thin sections, shows that Mishrif Formation comprises of six depositional environments, these are: deep marine, lagoon, rudist biostrome, back shoal, and shallow open marine. These environments have effect by many diagenetic processes, including dolomitization, dissolution, micritization, cementation, recrystallization and Stylolite, some of these processes have improved the reservoir properties of the Mishrif reservoir, these are: dissolution, dolomitization and the stylolization. The others diagenetic processes have negative influence on the Petrophysical properties, such as cementation, compaction, and recrystallization processes, which damage the porosity and decrease the pore size. The reservoir properties are controlled by deposition environment, where lagoon environment is mostly compact with low porosity, shoal environment reflects a high energy and grain-supported environment and has good reservoir potential, deep-marine environments consist of mudstone to wackestone, which represents low energy level with low porosity and represents the non-reservoir environment.